Seasonal development of Paeonia obovata and Paeonia oreogeton and their contents of biologically active and reserve substances in the forest-steppe zone of Western Siberia - Kalendar, Olga V.; Kostikova, Vera A.; Kukushkina, Tatiana A.; Erst, Andrey S.; Kuznetsov, Alexander A.; Kulikovskiy, Maxim S.; Vasilyeva, Olga Y. (Horticulturae)
Paeonia obovata and Paeonia oreogeton belong to the monotypic family Paeoniaceae. Both are popular as ornamental plants. P. obovata and P. oreogeton have been introduced into Novosibirsk Oblast (Western Siberia) from Primorye (Far East). The aim of the study was to assess their adaptability as well as the effect of seasonal developmental stages on the accumulation of secondary metabolites and reserve substances in the leaves and rhizomes under the conditions of Akademgorodok (Novosibirsk, Russia). According to long-term data (15 years), P. obovata and P. oreogeton complete the entire growth cycle here, including flowering and fruiting. Both species exhibited abundant flowering, but in the first 3 years, P. oreogeton did not bloom; yet under the microclimatic conditions specifically selected for this species (a more shaded area), it started to bloom and fruit yearly. A biochemical analysis (by spectrometric method) of P. obovata and P. oreogeton grown in Akademgorodok showed that the leaves accumulate higher concentrations of flavonols (P. obovata: 1.77%), tannins (P. oreogeton: 16.42%), ascorbic acid (P. oreogeton: 155.2 mg/100 g), and sugars (P. obovata: 20.85%) as compared to the roots. Peony rhizomes contain higher concentrations of protopectins (P. oreogeton: 13.03%), saponins (P. obovata: 21.06%), and starch (P. obovata: 30.20%) than the leaves do. These data can help to increase the levels of these natural compounds in these species. Further investigation into the dynamics of accumulation of biologically active substances in the organs of peonies will help to identify introduced plant species having high biochemical potential for the pharmaceutical industry.